Physicochemical properties and antioxidant activity of Spray-dried pomegranate (Punica Granatum) juice powder - Siti Faridah Mohd Amin; Tanujaa S Yavanathan; Nor Qhairul Izreen Mohd Noor; Ahmad Hazim Abdul Aziz (Malaysian Society of Agricultural and Food Engineers (MSAE), 2025)
This study aimed to investigate the effect of different carrier agents on the physicochemical properties and antioxidant activity of the spray-dried pomegranate juice. Maltodextrin and gum Arabic were used at 20% and 30%, respectively. The results revealed that spray-dried pomegranate juice with 20% gum Arabic exhibited higher drying yield and bulk density than other powders. Spray-dried powder with both concentrations of maltodextrin (20% and 30%) demonstrated higher water solubility and lower hygroscopicity and moisture content than that of gum Arabic. Anthocyanin content (4.64 mg/L), phenolic content (528.40 mg GAE/g), and antioxidant activity (1288.5 mM GAE/g DW for FRAP and 363.9mM GAE/g DW for DPPH) were all noticeably higher in powder with 20% maltodextrin compared to the powder encapsulated with gum Arabic. The type and concentration of carrier agent did not significantly affect the colour properties of the pomegranate juice powder.